The meaning of convenience in smart home imaginaries: tech industry insights. Issue 1 (28th June 2021) - Aagaard, Line Kryger
Smart home technology (SHT) is being promoted for the enhancement of occupants' convenience, as well as more efficient and sustainable energy consumption. However, recent research indicates that convenience often takes precedence over energy reduction, threatening to affect inhabitants' everyday practices in a non-sustainable way. In order to understand the social and environmental consequences of SHT, the meaning of convenience is investigated. How is the concept of convenience developed in concert with technological development? Presenting SHT imaginaries from the industry, the paper builds on qualitative interviews with 11 SHT professionals. By exploring the practices, roles, and relations at play in SHT development, it is demonstrated how the vision to enhance convenience in everyday life is related to a user imaginary characterized by passivity and disengagement from energy savings. Furthermore, convenience is enabled and enforced through the notion of interoperability. Interoperability refers to not only technologies 'speaking together' but also a strong interdependency between professional actors. By exploring the practices at play in SHT development, the meaning of convenience is revealed to be an outcome of this interdependency as well as the collectively shaped ideas, and technological standards embedded in the industry. Policy Relevance: SHT is shaping our domestic futures, influencing material environments as well as social life and energy consumption. Currently, SHT is promoted and supported widely in policy. For instance, the European Commission stresses automation as a means to ensure the more efficient operation of buildings, generating cost and energy savings. However, a focus on convenience risks counteracting sustainability considerations. This study shows how convenience can take precedence across various branches of SHT development, with a consequence of creating passive users who are disengaged from sustainability issues. When policymakers promote the adoption of SHTs and automation of the built environment, a more critical stance is needed toward convenience in order to avoid user passivity and masked energy consumption. Policy instruments, such as the smart readiness indicator (SRI), should not only include calculations of what is technically possible in terms of automation but also examine the outcomes, practices, and behavior that SHT promotes.